2020
DOI: 10.3389/fimmu.2020.00584
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Drinking Water Quality on Phagocyte Responses of Broiler Chickens Against Fungal and Bacterial Challenges

Abstract: Combinatorial effects of xenobiotics in water on health may occur even at levels within current acceptable guidelines for individual chemicals. Herein, we took advantage of the sensitivity of the immune system and an avian animal model to examine the impact of xenobiotic mixtures on animal health. Water was derived from an underground well in Alberta, Canada and met guidelines for consumption, but contained a number of contaminants. Changes to chicken immunity were evaluated following acute (7d) exposure to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Similar results were obtained in this experiment, as the broiler serum antibodies and biochemical parameters were not affected by the drinking water containing NaDCC. More-Bayona et al ( 41 ) reported an increase in macrophages and a decrease in CD8+ lymphocytes in the peritoneal cavity of broilers that consumed well water containing a mixture of biological preparations for an extended period. They also observed varying degrees of inflammatory responses in the organism caused by fungi and bacteria present in the water.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were obtained in this experiment, as the broiler serum antibodies and biochemical parameters were not affected by the drinking water containing NaDCC. More-Bayona et al ( 41 ) reported an increase in macrophages and a decrease in CD8+ lymphocytes in the peritoneal cavity of broilers that consumed well water containing a mixture of biological preparations for an extended period. They also observed varying degrees of inflammatory responses in the organism caused by fungi and bacteria present in the water.…”
Section: Discussionmentioning
confidence: 99%
“…Water represents an important requirement for all living organisms, as well as affects immune functions and homeostasis in broiler chickens ( More-Bayona et al , 2020 ). Water absence shortened the survival time among the broiler chickens ( Abbas et al , 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…The main factors influencing biofilm formation include the substrate's chemical composition, temperature, oxygen ( O 2 ) content, and interactions between microbes ( García-Gonzalo and Pagán, 2015 ). In addition to pathogenic microorganisms, water can also be contaminated with harmful xenobiotics that can cause an increase in macrophages, decrease the number of CD8+ lymphocytes, and initiate inflammatory reactions in the body ( More-Bayona et al, 2020 ). Heavy metals such as copper ( Cu ) and lead ( Pb ) are other pollutants.…”
Section: Immunosafety and Immune Securitymentioning
confidence: 99%